The Australian Institute of Sport (AIS) framework for rebooting sport in a COVID-19 environment (Australian Institute of Sport, 2020)
The Australian Institute of Sport (AIS) and Sport Australia welcome the release by National Cabinet of the National Principles for the Resumption of Sport and Recreation Activities, which provides the pathway for a safe return to sport.